2022
DOI: 10.1055/s-0042-1750388
|View full text |Cite
|
Sign up to set email alerts
|

Long-Delayed Manifestation of COVID-19 Coagulopathy Presenting with Severe Cerebral Venous Thrombosis Causes Massive Brain Hemorrhage

Abstract: COVID-19 infection causes coagulopathy, which may lead to cerebral venous thrombotic (CVT) event. It usually occurs in patients with higher severity level of infection and manifests mostly within a month after the infection. However, in rare cases, the CVT may happen long after the infection and unrelated to the degree of the infection severity. We present the case of a previously healthy 62-year-old male patient with very mild COVID-19 symptoms that resolved in 3 weeks of home isolation treatment. Immediately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…16 The median time duration from COVID infection to CVT diagnosis reported is seven days (range 1–120 days). 9, 3539 The largest multicentric observational study published consisting of 20 patients also reported a male predominance (70%) and a mean age of 42.4 years at the time of presentation. 9 Traditionally, non-COVID-CVT is more common in young females (59%–75%), mostly in their second and third decades of life.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…16 The median time duration from COVID infection to CVT diagnosis reported is seven days (range 1–120 days). 9, 3539 The largest multicentric observational study published consisting of 20 patients also reported a male predominance (70%) and a mean age of 42.4 years at the time of presentation. 9 Traditionally, non-COVID-CVT is more common in young females (59%–75%), mostly in their second and third decades of life.…”
Section: Discussionmentioning
confidence: 98%
“…CVT in COVID sufferers usually manifests within one month of infection but the case has also been reported as a late sequala. 36, 39 Table 1 includes a summary of the published studies of CVT in COVID patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations